Tourist satisfaction factors via analytic hierarchy process decision model on cultural-tourism in Kota Kinabalu, Sabah - Ramamoorty Thavamalar; Abdullah, N. (Akademi Sains Malaysia, 2020)
In recent years, the tourism and hospitality industry has shown a deepening diversified growth and has become internationally a quick and growing industry that contributes the most in the economic development. Tourism plays a vital role in promoting a country's cultural and heritage, while cultural tourism covers all the travelling aspects, whereby the local people educate tourists with their own living ways, beliefs and thoughts. Other resources have stated that cultural tourism involves high values of places related to tourism, history and heritage. As there are several places in Sabah that exhibit great values in history and heritage of the local people, there is a need to evaluate the best decision-making of multiple criteria in the field of cultural tourism. Factors are identified using the Analytic Hierarchy Process (AHP) in terms of tourists' preferability, especially in the selection of cultural tourism spots in Sabah as their place of visitation. The objectives of this study are to evaluate and compare the preferability of tourists visiting the cultural-tourism locations, and to identify the significant factors that attract the tourists to visit these cultural-tourism spots. Prior to the data analysis, 150 respondents through questionnaires will be randomly selected at different cultural-tourism spots in Kota Kinabalu, Sabah. The data will be analysed using the AHP method, with the aid of Saaty 1-9 scale. The AHP decision model in this study was developed with the aid of model-building procedures like the normal matrix of z-scores and mean scores, and the pairwise comparison matrix of weights of criteria and sub-criteria. Based on the overall AHP analysis, it was found that the Destination criterion was ranked the highest at 52.51%, followed by criterion of Benefits with weight of 22.36%, partially ranked at 14.29% was Activities criterion, the criterion of Safety earned the weight 6.94%, and lastly the lowest ranking for Services criterion at 3.90%. From the analysis, it can be concluded that the most important factor in Cultural tourism was the Destination of the cultural spots. © 2020.